Physics 1250 Vector, Matrix & Complex Analysis Physical Quantities that have directions and magnitudes are commonly called as vectors. Examples of vectors are velocity, acceleration, force, torque, momentum etc. Vectors can be added, subtracted multiplied but cannot be “divided”. β and βπ be two vectors. To get the sum of the two vectors, place the tail of βπ onto the head of π β Let π β β to the head of π. The distance between the tail of π β and head of and then draw an arrow from the tail of π βπ is |π β β β + π | and the vector sum is π β + π. β + πβ π O O βπ¨ = |π¨π |π Μ + |π¨π |π Μ + |π¨π |πΜ βπ¨ = [|π¨π | − π] π Μ + [|π¨π | − π] π Μ + [|π¨π | − π] πΜ (Ax , Ay ,Az) (0, 0, 0) β| |π βπ βββββββββββ |π + π| βββββββββββ π+π β π |π β| Given the vectors: β = −ππ Μ − π Μ + ππΜ π¨ ββ = −ππ Μ + ππ Μ − πΜ π© β = π¨ β + π© ββ = −ππ Μ + ππ Μ + πΜ πͺ β | = √(−π)π + (π)π + ππ = √ππ πππππ |πͺ So the vector sum βπͺ has coordinates (-5, 2, 1) for its head; and the tail is at the origin. Tail coordinates (1, 2, 1) and Head coordinates (2, 0, 2), the expression for the vector is: ββ = (π − π)π Μ + (π − π)π Μ + (π − π)πΜ π½ ββ | = √ππ + (−π)π + ππ = √π πππππ |π½ Example βπ¨ β = −π Μ +ππ Μ + ππΜ | βπ¨| = √π + π + π = √ππ πππππ What is the direction of the vector? From the definition of a vector, βπ¨ β = | βπ¨ β |π Μ The direction is therefore, Μ= π Μ = π Μ +ππ Μ + ππΜ −π √ππ β π¨ ββ | |π¨ |π Μ| = ? In matrix form, the previous vectors are −π −π βπ¨ β = (−π) , βπ© β = (π) π −π ππ −π βπ¨ + βπ© β = [π¨] + [π©] = ( π ) π β π΄ − π΅ β π΅ β π΄+ π΅ β π΅ π΄ IS NOT THE SAME π΄ π΄ β −π΅ β π΄ + −π΅ β| |π βπ βββββββββββ |π + π| βββββββββββ π+π β π |π β| Multiplication of a vector by a positive scalar k multiplies the magnitude but leaves the direction β just doubles the magnitude only but the direction unchanged. If k = 2 then the magnitude of π remains the same. Multiplication of Vectors Multiplication of a vector by a positive scalar k multiplies the magnitude but leaves the direction unchanged. If k = 2, β just doubles but the direction then the magnitude of vector π remains the same. See figure on the right: β 2π β π Dot product of two vectors - is the product of a vector to the projection of the other vector It is just the vector product of two parallel or antiparallel vectors. If the vectors are neither parallel or antiparallel, then the component (|π| cos π) is the one to be multiplied to the other component βπ. β cos π π β π θ βπ β π β| |π β π θ θ |π β| β |πππ π½ |π β β βπ is called the dot product of the two vectors, defined by The dot product π β | ππ π‘βπ π‘π€π π£πππ‘πππ πππ ππππππππ |π β ||π β | cos π = {−|π β β βπ = |π β ||π π β | ππ π‘βπ π‘π€π π£πππ‘πππ πππ πππ‘πππππππππ β ||π 0 ππ π‘βπ π‘π€π π£πππ‘πππ πππ ππππππππππ’πππ ββ πππ π© ββ ππ π£πππ‘πππ Example: Let π¨ βπ© β = 3π₯Μ βπ¨ = 2π₯Μ ππππππππ ββ = 3π₯Μ π© β = 2π¦Μ π¨ ββ β π© ββ = (2)(3) cos 90 = 0 ππππππππππ’πππ = π¨ βπ© β = 3π₯Μ βπ¨ = −2π₯Μ πππ‘πππππππππ βπ¨ β βπ© β = (2)(3) cos 0 = 6 π’πππ‘π βπ¨ β βπ© β = (2)(3) cos 180 = −6 π’πππ‘π ββ β π© ββ = 2(−π₯Μ) β 3π₯Μ = (2)(3) [(−π₯Μ) β (π₯Μ)] = 6 [(1)(1) cos 180] = −6 π’πππ‘π π¨ β πππ π© ββ ππ π£πππ‘πππ Example: Let π¨ βπ¨ = 3π₯Μ + 2π¦Μ πππ βπ© β = π§Μ β β π© ββ = (3π₯Μ + 2π¦Μ) β π§Μ = 0 , π‘βπ π£πππ‘πππ πππ ππππππππππ’πππ π¨ Example: Let βπ¨ = 2π₯Μ − π¦Μ + 2π§Μ πππ βπ© β = −2π₯Μ + 2 π¦Μ − π§Μ ββ β π© ββ = (2π₯Μ − π¦Μ + 2π§Μ ) β (−2π₯Μ + 2 π¦Μ − π§Μ ) π¨ = (2π₯Μ) β (−2π₯Μ + 2 π¦Μ − π§Μ ) + (− π¦Μ) β (−2π₯Μ + 2 π¦Μ − π§Μ ) + (2π§Μ ) β (−2π₯Μ + 2 π¦Μ − π§Μ ) = [−4] + [−2] + [−2] = −8 Example: Let π΄ = 2π₯Μ − π¦Μ + 2π§Μ β = −2π₯Μ + 2 π¦Μ − π§Μ find the angle between them πππ π΅ Using the definition: β = |π΄||π΅| cos π π΄βπ΅ cos π = −8 8 = − (3)(3) 9 → β π΄βπ΅ = cos π |π΄||π΅| → 8 π = arccos [− ] 9 β = |π΄||π΅| sin π πΜ = [|π΄||π΅| sin π] πΜ , Cross Product of any two vectors is defined by π΄ π₯ π΅ Μ is a unit vector (vector of length 1) pointing where πΜ = π β πͺ β . But as there are β πππ π perpendicular to the plane of π two directions perpendicular to any plane, the ambiguity is resolved by the right hand rule: let your fingers point in the direction of the first vector and curl around (via the smaller angle) towards the second; then your thumb indicates the direction of the unit vector. πΜ Plane defined the vectors π πππ πβ which area is |π||πβ | sin π β π θ β π Unit vector is a vector whose magnitude is 1 and points to a particular direction. Without loss of generality, we can assume π₯Μ = π, π¦Μ = π, π§Μ = π to be three distinct unit vectors along the x, y, and z-axis relatively. y-axis j i k z-axis Applying the Dot Product definition, x-axis π₯Μ β π₯Μ = 1 π¦ { Μ β π₯Μ = 0 π§Μ β π₯Μ = 0 , , , π₯Μ β π¦Μ = 1 π¦Μ β π¦Μ = 1 π§Μ β π¦Μ = 0 , , , π₯Μ β π§Μ = 1 π¦Μ β π§Μ = 1 π§Μ β π§Μ = 1 Likewise applying the Cross Product definition, π₯Μ × π₯Μ = 0 , {π¦Μ × π₯Μ = −π§Μ , π§Μ × π₯Μ = π¦Μ , π₯Μ × π¦Μ = π§Μ , π¦Μ × π¦Μ = 0 , π§Μ × π¦Μ = −π₯Μ , π₯Μ × π§Μ = −π¦Μ π¦Μ × π§Μ = π₯Μ π§Μ × π§Μ = 0 A simplified guide to this definition is achieved by using the cyclic permutation as shown where counterclockwise permutation is considered positive and clockwise permutation is negative. Neither clockwise or counterclockwise gives the zero cross product. π₯Μ π¦Μ π§Μ β = π΄π πΜ + π΄π πΜ + π΄π§ π§Μ , where πΜ, πΜ, π§Μ are the unit In cylindrical coordinate systems, a vector π¨ vectors of the coordinate system. From rectangular to cylindrical π = √π₯ 2 + π¦ 2 π¦ π = π‘ππ−1 π₯ π§ = π§ From cylindrical to rectangular π₯ = π cos π π¦ = π cos π π§ = π§ π − ππππ π − ππππ π − ππππ π π Μ πππ π −π π − ππππ Μ π Μ πππ π π π π Μ −π π Μ π Μ π π − ππππ π Unit Vectors: Cylindrical to rectangular Μ = πππ π π Μ − πππ π π Μ π Μ = πππ π π Μ + πππ π π Μ π πΜ = πΜ In matrix form: πππ π Μ π (π ) = ( Μ πππ π π πΜ Μ − πππ π π π ) ( πππ π π π Μ) π π πΜ β = π΄π πΜ + π΄π πΜ + π΄π πΜ, where πΜ , πΜ, πΜ are the unit In spherical coordinate system, a vector π¨ vectors of the coordinate system. Examples of Cross Product π΄ = 2π₯Μ − π¦Μ + 2π§Μ β = −2π₯Μ + 2 π¦Μ − π§Μ πππ π΅ β = 2π₯Μ π₯ (−2π₯Μ + 2 π¦Μ − π§Μ ) + (−π¦Μ) π₯ (−2π₯Μ + 2 π¦Μ − π§Μ ) + 2π§Μ π₯ (−2π₯Μ + 2 π¦Μ − π§Μ ) π΄ π₯ π΅ β = 2π₯Μ π₯ (2 π¦Μ − π§Μ ) + (−π¦Μ) π₯ (−2π₯Μ − π§Μ ) + 2π§Μ π₯ (−2π₯Μ + 2 π¦Μ) π΄ π₯ π΅ β = (4π§Μ + 2π¦Μ) + (−2π§Μ + π₯Μ) + (−4π¦Μ − 4π₯Μ) = −ππ Μ − ππ Μ + ππΜ π΄ π₯ π΅ π₯Μ π¦Μ β π΄ π₯ π΅ = | 2 −1 −2 2 π§Μ π₯Μ π¦Μ π§Μ π₯Μ π¦Μ 2 | → | 2 −1 2 | 2 −1 = (π₯Μ − 4π¦Μ + 4π§Μ ) − (4π₯Μ − 2π¦Μ + 2π§Μ ) −1 −2 2 −1 −2 2 π₯Μ π¦Μ β π΄ π₯ π΅ = | 2 −1 −2 2 π§Μ Μ − ππ Μ + ππΜ 2 | = (π₯Μ − 4π¦Μ + 4π§Μ ) − (4π₯Μ − 2π¦Μ + 2π§Μ ) = −ππ −1 Vector Practice 1. Consider three vectors: π΄ = 3π₯Μ + 0π¦Μ β = 2√3π₯Μ + 2π¦Μ {π΅ πΆ = −5π₯Μ + 5√3π¦Μ a. With three vectors, find the angles between vectors, and find the vector sum. b. What is the length or magnitude of A , B and C ? Length of the vector A ο½ A ο½ Ax2 ο« Ay2 = ? Length of the vector B ο½ B ο½ Bx2 ο« B y2 = ? Length of the vector C ο½ C ο½ C x2 ο« C y2 = ? c. What is the angle between A and C , A and B , B and C ? We know that A ο C = A C cos ο± , ο© οΉ AοC οΊ So, ο± ο½ cos ο1 οͺ οͺA CοΊ AC ο« ο» Now, π΄ β πΆ = π΄π₯ π₯Μ + π΄π¦ π¦Μ β πΆπ₯ π₯Μ + πΆπ¦ π¦Μ = Ax C x ο« Ay C y So, cos ο± ο½ So, cos ο± ο½ AοC AοC AC ο ο± ο½ either ? or ?. But notice that the y-component of C is positive and the x-component negative. So it is in the 2nd quadrant and the A vector is in the first quadrant. So, the angle between them cannot be more than ?. 180ο° . So the angle between A and C is Similarly, the angle between A and B is Aο B , cos ο± ο½ AB cos ο± ο½ Aο B = ? ο ο± ο½ either ? or ?. But ο± οΉ 330ο° , as none of the components AB of A and B are negative. So, ο ο± ο½ ? Similarly, the angle between B and C is B οC cos ο± ο½ , BC cos ο± ο½ B οC = ? ο ο± ο½ either ? or ?. But ο± οΉ 270ο° , as none of the BC components of B and C are negative. So, ο ο± ο½ ? 2. Consider three vectors: π΄ = 4π₯Μ + 6π¦Μ − 2π§Μ β = 2π₯Μ + 7π¦Μ − π§Μ {π΅ πΆ = 0π₯Μ + 3π¦Μ + 5π§Μ a. What is the length or magnitude of A , also written as A ? Length of the vector A ο½ Ax2 ο« Ay2 ο« Az2 = 4 2 ο« 6 2 ο« (ο2) 2 = b. Write the expression for 2 A . 2 A = 2( A ) = 2(4π₯Μ + 6π¦Μ − 2π§Μ ) = ? c. What is A ο« B ? A ο« B = π΄π₯ π₯Μ + π΄π¦ π¦Μ + π΄π§ π§Μ + π΅π₯ π₯Μ + π΅π¦ π¦Μ + π΅π§ π§Μ ? = (π΄π₯ + π΅π₯ )π₯Μ + π΄π¦ + π΅π¦ π¦Μ + (π΄π§ + π΅π§ )π§Μ d. What is C ο A ? C ο A = πΆπ₯ π₯Μ + πΆπ¦ π¦Μ + πΆπ§ π§Μ − π΄π₯ π₯Μ + π΄π¦ π¦Μ + π΄π§ π§Μ = (πΆπ₯ − π΄π₯ )π₯Μ + πΆπ¦ − π΄π¦ π¦Μ + (πΆπ§ − π΄π§ )π§Μ e. What is C ο΄ A ? With π΄ = 4π₯Μ + 6π¦Μ − 2π§Μ β = 2π₯Μ + 7π¦Μ − π§Μ {π΅ πΆ = 0π₯Μ + 3π¦Μ + 5π§Μ C ο΄ A = πΆπ₯ π₯Μ + πΆπ¦ π¦Μ + πΆπ§ π§Μ × π΄π₯ π₯Μ + π΄π¦ π¦Μ + π΄π§ π§Μ π₯Μ πΆ × π΄ = | πΆπ₯ π΄π₯ πΆ×π΄ = π¦Μ πΆπ¦ π΄π¦ π§Μ πΆ πΆπ§ | = | π¦ π΄π¦ π΄π§ πΆπ§ πΆ | π₯Μ − | π₯ π΄π§ π΄π₯ πΆπ₯ πΆπ§ | π¦Μ + | π΄π§ π΄π₯ πΆπ¦ | π§Μ π΄π¦ πΆπ¦ π΄π§ − πΆπ§ π΄π¦ π₯Μ − (πΆπ₯ π΄π§ − πΆπ§ π΄π₯ )π¦Μ + πΆπ₯ π΄π¦ − πΆπ¦ π΄π₯ π§Μ πΆ × π΄ = [3(−2) − 5(6)]π₯Μ − [0 − 5(4)]π¦Μ + [0 − 3(4)]π§Μ πΆ × π΄ = [3(−2) − 5(6)]π₯Μ − [0 − 5(4)]π¦Μ + [0 − 3(4)]π§Μ πΆ × π΄ = −36π₯Μ + 20π¦Μ − 12π§Μ f. What is the magnitude of C ο΄ A ? Magnitude of C ο΄ A = C ο΄ A Let us name C ο΄ A = M Then magnitude of M = M ο½ M x2 ο« M y2 ο« M z2 = 4 115 g. What is B ο C ? B ο C = Bx C x ο« B y C y ο« Bz C z = 2 ο 0 ο« 7 ο 3 ο« (ο1) ο 5 =16 Note: B ο C is the dot product of the two vectors. B ο C = B C cos ο± , where ο± is the angle formed by B and C when they are place tail-to-tail. h. What is the angle between A and C ? ο² ο² We know that A ο C = A C cos ο± , So, cos ο± ο½ AοC AC ο© οΉ AοC οΊ οͺ So, ο± ο½ cos οͺA CοΊ ο« ο» ο¦ οΆ ο¦ 2 οΆ 8 So ο± ο½ cos ο1 ο§ο§ ο·ο· ο½ cos ο1 ο§ο§ ο·ο· ο¨ 2 14 ο΄ 34 οΈ ο¨ 119 οΈ ο1 i. Does B ο C equal C ο B ? Yes. We can see that B ο C is a scalar (hence the alternative name scalar product). So the dot product is commutative. That is B ο C = C ο B j. How is C ο΄ A and Aο΄ C related? Using the formula for the cross product, πΆ × π΄ = πΆπ₯ π₯Μ + πΆπ¦ π¦Μ + πΆπ§ π§Μ × π΄π₯ π₯Μ + π΄π¦ π¦Μ + π΄π§ π§Μ π₯Μ πΆ × π΄ = | πΆπ₯ π΄π₯ πΆ×π΄ = π¦Μ πΆπ¦ π΄π¦ π§Μ πΆ πΆπ§ | = | π¦ π΄π¦ π΄π§ πΆπ§ πΆ | π₯Μ − | π₯ π΄π§ π΄π₯ πΆπ₯ πΆπ§ | π¦Μ + | π΄π§ π΄π₯ πΆπ¦ | π§Μ π΄π¦ πΆπ¦ π΄π§ − πΆπ§ π΄π¦ π₯Μ − (πΆπ₯ π΄π§ − πΆπ§ π΄π₯ )π¦Μ + πΆπ₯ π΄π¦ − πΆπ¦ π΄π₯ π§Μ And π΄ × πΆ = π΄π₯ π₯Μ + π΄π¦ π¦Μ + π΄π§ π§Μ × πΆπ₯ π₯Μ + πΆπ¦ π¦Μ + πΆπ§ π§Μ π₯Μ π΄ π΄×πΆ = | π₯ πΆπ₯ π΄×πΆ = π¦Μ π΄π¦ πΆπ¦ π§Μ π΄ π΄π§ | = | π¦ πΆπ¦ πΆπ§ π΄π§ π΄ | π₯Μ − | π₯ πΆπ§ πΆπ₯ π΄π₯ π΄π§ | π¦Μ + | πΆπ§ πΆπ₯ π΄π¦ | π§Μ πΆπ¦ π΄π¦ πΆπ§ − π΄π§ πΆπ¦ π₯Μ − (π΄π₯ πΆπ§ − π΄π§ πΆπ₯ )π¦Μ + π΄π₯ πΆπ¦ − π΄π¦ πΆπ₯ π§Μ π΄ × πΆ = − πΆπ¦ π΄π§ − πΆπ§ π΄π¦ π₯Μ + (πΆπ₯ π΄π§ − πΆπ§ π΄π₯ )π¦Μ − πΆπ₯ π΄π¦ − πΆπ¦ π΄π₯ π§Μ Equating 1) and 2), we can clearly see that ( C ο΄ A ) = β ( Aο΄ C ) k. Give an example of the use of dot product in Physics and explain. Mechanical work is a dot product between the force and the displacement. W ο½ F οr It means that the work is amount of displacement times the projection of force along the displacement. l. Give an example of the use of cross product in Physics and explain. Magnetic force is a good example of a cross product of velocity of a charged particle times the magnetic field. ο² ο² ο² F ο½ q(v ο΄ B) It means that the force is perpendicular to both v and B , and that the magnitude of the force is equal to the area of the parallelogram they span. m. Imagine that the vector A is a force whose units are given in Newtons. Imagine vector B is a radius vector through which the force acts in meters. What is the value of the torque (ο΄ ο½ r ο΄ F ) , in this case? Torque is the cross product between the radius (lever arm) vector and the force vector, (ο΄ ο½ r ο΄ F ) . β πππ πΉ = π΄, so that, in this case ο΄ ο½ B ο΄ A . Using the given expressions of vectors, Let π = π΅ π΄ = 4π₯Μ + 6π¦Μ − 2π§Μ β = 2π₯Μ + 7π¦Μ − π§Μ {π΅ πΆ = 0π₯Μ + 3π¦Μ + 5π§Μ β × π΄ = π΅π₯ π₯Μ + π΅π¦ π¦Μ + π΅π§ π§Μ × π΄π₯ π₯Μ + π΄π¦ π¦Μ + π΄π§ π§Μ π΅ π₯Μ β × π΄ = | π΅π₯ π΅ π΄π₯ β ×π΄ = π΅ π¦Μ π΅π¦ π΄π¦ π§Μ π΅ π΅π§ | = | π¦ π΄π¦ π΄π§ π΅π§ π΅ | π₯Μ − | π₯ π΄π§ π΄π₯ π΅π₯ π΅π§ | π¦Μ + | π΄π§ π΄π₯ π΅π¦ | π§Μ π΄π¦ π΅π¦ π΄π§ − π΅π§ π΄π¦ π₯Μ − (π΅π₯ π΄π§ − π΅π§ π΄π₯ )π¦Μ + π΅π₯ π΄π¦ − π΅π¦ π΄π₯ π§Μ π = [7(−2) − (−1)(6)]π₯Μ − [2(−2) − (−1)(4)]π¦Μ + [2(6) − 7(4)]π§Μ π = 8π₯Μ − 0π¦Μ − 16π§Μ = 8π₯Μ − 16π§Μ π. π n. Now imagine that A continues to be a force vector and C is a displacement vector whose units are meters. What is the work done in applying force A through a displacement C ? Work done in applying force A through a displacement C is W ο½ AοC = ( Ax iˆ ο« Ay ˆj ο« Az kˆ) ο (C x iˆ ο« C y ˆj ο« C z kˆ) W = Ax C x ο« Ay C y ο« Az C z = 4 ο 0 ο« 6 ο 3 ο« (ο2) ο 5 = 8 joules ο² ο² o. What is the vector sum of a vector D given by 40 m, 30 degrees and a vector E given by 12 m, 225 degrees? Use the method of resolving vectors into their components and then adding the components. Let us start by resolving the vectors into their x-components and y-components. It can be assumed that the angles given in the question are w.r.t the x-axis. ο² For D : ο² ο² The magnitude of D = D is 40 and the angle is 30o ο² ο² So, as the projection of D along the x-axis = D cos ο± 3 Dx = 40 cos 30 = 40 ο ο½ 20 3 2 ο² ο² The projection of D along the y-axis = D sin ο± 1 D y ο½ 40 sin 30 ο½ 40 ο ο½ 20 2 ο² Similarly for E : ο¦ ο1 οΆ E x ο½ 12 cos 225 ο½ 12 ο ο§ ο· ο½ ο6 2 ο¨ 2οΈ ο¦ ο1 οΆ E y ο½ 12 sin 225 ο½ 12 ο ο§ ο· ο½ ο6 2 ο¨ 2οΈ ο² ο² So, D + E = ( Dx xˆ ο« D y yˆ ) ο« ( E x xˆ ο« E y yˆ ) = ( Dx ο« E x ) xˆ ο« ( D y ο« E y ) yˆ = (20 3 ο 6 2 ) xˆ ο« (20 ο 6 2 ) yˆ 3. Consider three vectors: ο² A ο½ ο3iˆ ο« 3 ˆj ο« 2kˆ ο² B ο½ ο2iˆ ο 4 ˆj ο« 2kˆ ο² C ο½ 2iˆ ο« 3 ˆj ο« 1kˆ ο² ο² ο² a. Find A ο ( B ο« C ) . First we shall find ο² ο² B ο« C = ( Bx iˆ ο« B y ˆj ο« Bz kˆ) ο« (C x iˆ ο« C y ˆj ο« C z kˆ) = ( Bx ο« C x )iˆ ο« ( B y ο« C y ) ˆj ο« ( Bz ο« C z )kˆ = ((ο2) ο« 2)iˆ ο« ((ο4) ο« 3) ˆj ο« (2 ο« 1)kˆ = 0iˆ ο 1 ˆj ο« 3kˆ ο² ο² ο² Let us name B ο« C ο½ E ο² ο² ο² ο² ο² Now, A ο ( B ο« C ) = A ο E ο½ ( Ax iˆ ο« Ay ˆj ο« Az kˆ) ο ( E x iˆ ο« E y ˆj ο« E z kˆ) = Ax E x ο« Ay E y ο« Az E z = (ο3) ο 0 ο« 3 ο (ο1) ο« 2 ο 3 =3 ο² ο² ο² b. Find A ο ( B ο΄ C ) . First we shall find ο² ο² B ο΄ C = ( Bx iˆ ο« B y ˆj ο« Bz kˆ) ο΄ (C x iˆ ο« C y ˆj ο« C z kˆ) = iˆ Bx Cx ˆj By Cy kˆ Bz Cz = ( B y C z ο Bz C y )iˆ ο ( Bx C z ο Bz C x ) ˆj ο« ( Bx C y ο B y C x )kˆ = ((ο4) ο 1 ο 2 ο 3)iˆ ο ((ο2) ο 1 ο 2 ο 2) ˆj ο« ((ο2) ο 3 ο (ο4) ο 2)kˆ = ο 10iˆ ο« 6 ˆj ο« 2kˆ ο² ο² ο² Let us name B ο΄ C ο½ D ο² ο² ο² ο² ο² Now, A ο ( B ο΄ C ) = A ο D ο½ ( Ax iˆ ο« Ay ˆj ο« Az kˆ) ο ( Dx iˆ ο« D y ˆj ο« Dz kˆ) = Ax Dx ο« Ay D y ο« Az Dz = (ο3) ο (ο10) ο« 3 ο 6 ο« 2 ο 2 = 52 ο² ο² ο² c. Find A ο΄ ( B ο« C ) . First we shall find ο² ο² B ο« C = ( Bx iˆ ο« B y ˆj ο« Bz kˆ) ο« (C x iˆ ο« C y ˆj ο« C z kˆ) = ( Bx ο« C x )iˆ ο« ( B y ο« C y ) ˆj ο« ( Bz ο« C z )kˆ = ((ο2) ο« 2)iˆ ο« ((ο4) ο« 3) ˆj ο« (2 ο« 1)kˆ = 0iˆ ο 1 ˆj ο« 3kˆ ο² ο² ο² Let us name B ο« C = F ο² ο² ο² ο² ο² Now A ο΄ ( B ο« C ) = A ο΄ F ο² ο² A ο΄ F = ( Ax iˆ ο« Ay ˆj ο« Az kˆ) ο΄ ( Fx iˆ ο« Fy ˆj ο« Fz kˆ) = iˆ ˆj kˆ Ax Fx Ay Fy Az Fz = ( Ay Fz ο Az Fy )iˆ ο ( Ax Fz ο Az Fx ) ˆj ο« ( Ax Fy ο Ay Fx )kˆ = (3 ο 3 ο 2 ο (ο1))iˆ ο ((ο3) ο 3 ο 2 ο 0) ˆj ο« ((ο3) ο (ο1) ο 3 ο 0)kˆ = 11iˆ ο« 9 ˆj ο« 3kˆ Prove the following: βπ¨ π βπ© β π βπͺ = βπ¨ β βπͺ βπ© β − βπ¨ β βπ© β βπͺ β = π© β − πͺ β π¨ β π π© ββ π πͺ ββ π¨ β βπͺ β βπ© ββ π¨ Reciprocal of a Vector Reciprocal of a Vector in One-Dimensional Basis For a single 3-D vector, say ββ = |π΄|π Μ π¨ (1) The reciprocal vector is one that is directed in the same direction as the given vector A, but has magnitude equal to 1 β −1 = ππππππ‘π’ππ ππ π¨ |π΄| So, the reciprocal vector β −1 = π¨ 1 Μ π |π΄| From equation (1) β β π π¨ π¨ β −1 = ( )[ ] = π¨ |π¨| |π¨| |π¨|π Therefore for the given single vector βββ Μ − 2π Μ + 5πΜ π¨ = 3π 2 βββ | = (3)2 + (−2)2 + (5)2 |π¨ The |π΄|2 = 38 , so the reciprocal vector of the given single vector βπ¨ is 1 Μ − 2π Μ + 5πΜ) (3π 38 βπ¨− 1 = Given: π΄ = 3π₯Μ − 2π¦Μ + 2π§Μ Find: β = π‘βπ ππππππππππ ππ π‘βπ πππ£ππ π£πππ‘ππ π΅ β =1 π΄ β π΅ → Looking for β = π΅ π΄ |π΄| 2 = 3π₯Μ − 2π¦Μ + 2π§Μ 3π₯Μ − 2π¦Μ + 2π§Μ = 2 2 + (−2) + (2) 17 (3)2 To check β ?ΜΏ 1 π΄ β π΅ (3π₯Μ − 2π¦Μ + 2π§Μ ) β Take for example, Look for the Reciprocal of the vector of, 3π₯Μ − 2π¦Μ + 2π§Μ 17 = = 1 17 17 β = −2π₯Μ − 3π¦Μ + 2π§Μ π¨ β −1 = π¨ −2π₯Μ − 3π¦Μ + 2π§Μ 17 Reciprocal of Vectors in Two-Dimensional Basis β ,π© ββ , it is not easy to do this but such difficulty can be by-passed For 2 given 3-D vectors π¨ Μ . For this, the cyclic permutation by considering an additional vector which is a unit vector π β [π΄ π΅ πΆ ] can be helpful. β = πΆ, π΅ β ×πΆ = π΄, πΆ×π΄ = π΅ β . This applies to [π¨ β π© ββ π Μ ], where π Μ is the unit That is, π΄ × π΅ Μ. In equation form, vector normal to the plane formed by the other 2 vectors and πΆ = |πΆ |π β = |π¨ β π₯π© ββ |πΜ = |πΆ |π Μ π΄×π΅ , Μ= π β ×πΆ = π΄ π΅ β π₯π© ββ π¨ β π₯π© ββ | |π¨ , β πΆ×π΄=π΅ Note that for β ×πΆ = π΄ π΅ β |π βπ© β × |πͺ Μ = βπ¨ βπ¨ = βπ© β × |π¨ β π₯ βπ© β |π β π₯ βπ© β | { βπ© β ×π Μ = |π¨ Μ} → β , is therefore The reciprocal of vector π¨ ββ π₯ π π© Μ βπ¨− 1 = β π₯π© ββ | |π¨ βπ¨− 1 = βπ© β −1 = ββ π₯ (π¨ β π₯π© ββ ) π© ββ π₯ βπ© β| |π¨ β π Μπ₯π¨ β π₯π© ββ | |π¨ βπ© β −1 = 2 ββ π₯ π© ββ ) π₯ π¨ β (π¨ ββ π₯ βπ© β| |π¨ 2 Cite your own examples ββ = ππ Μ − ππ Μ + ππΜ π¨ π₯Μ ββ π₯ π© ββ = |3 π¨ 1 π¦Μ π§Μ −2 3| = [(−2)2 − 3(4)]π₯Μ − [3(2) − 3(1)]π¦Μ + [3(4) − (−2)]π§Μ 4 2 2 βπ¨ β π₯ βπ© β = −16π₯Μ − 3π¦Μ + 14π§Μ Note that, ββ = π Μ + ππ Μ + ππΜ π© β π₯ βπ© β | = 256 + 9 + 196 = 461 |π¨ π₯Μ π¦Μ π§Μ ββ × π¨ β × π© ββ = | 1 π© 4 2 | = 62π₯Μ − 46π¦Μ + 61π§Μ −16 −3 14 β is The reciprocal of vector βπ¨ βπ¨− 1 = βπ© β π₯ (π¨ ββ π₯ βπ© β) β π₯π© ββ | |π¨ 2 = 62π₯Μ − 46π¦Μ + 61π§Μ 461 To check, ββ β βπ¨− 1 = 1 ? π¨ βπ¨ β = ππ Μ − ππ Μ + ππΜ ββ β βπ¨− 1 = π¨ βπ¨ β −1 = 62π₯Μ − 46π¦Μ + 61π§Μ 461 3(62) + 2(46) + 3(61) = 1 461 Find βπ© β −1 = β π₯ βπ© β ) π₯ βπ¨ (π¨ ββ π₯ π© ββ | |π¨ 2 =? Reciprocal of Vectors in Three-Dimensional Basis: Reciprocal Lattice β and βπͺ , we consider the cyclic permutation [π΄π΅ β πΆ ] which is For 3 given 3-D vectors βπ¨, βπ© actually expressed commonly as, β πΆ] = π΄ β π΅ β ×πΆ =π [π΄π΅ β ] = πΆβπ΄×π΅ β =π [πΆ π΄π΅ β πΆ π΄] = π΅ β βπΆ×π΄ =π [π΅ In writing the first scalar triple product, β ×πΆ π΄ β π΅ =1 π → π΄ β { β ×πΆ π΅ } =1 π It is apparent that β ×πΆ β ×πΆ π΅ π΅ = π β ×πΆ π΄ β π΅ π΄−1 = Writing the other scalar triple product, β β πΆ×π΄ π΅ =1 π It is apparent that β −1 = π΅ πΆ×π΄ πΆ×π΄ = π β ×πΆ π΄ β π΅ Lastly for the scalar triple product, β πΆ β π΄×π΅ =1 π πΆ −1 = Cite your own examples β β π΄×π΅ π΄×π΅ = π β ×πΆ π΄ β π΅ Inverse of Matrix π¨ππ [π¨] = [π¨ππ π¨ππ π¨ππ π¨ππ π¨ππ π¨ππ π π¨ππ ] = [π π¨ππ π π π π −π] π π Minor of π¨ππ : Is the determinant of the submatrix after eliminating (deleting) the row and column where A11 is located. π¨ π¨ππ π ππ [ ππ ] = [π¨ππ π¨ππ − π¨ππ π¨ππ ] = π π¨ππ π¨ππ Minor of π¨ππ : Is the determinant of the submatrix after eliminating (deleting) the row and column where A12 is located. π¨ π¨ππ π ππ [ ππ ] = [π¨ππ π¨ππ − π¨ππ π¨ππ ] = π π¨ππ π¨ππ Minor of π¨ππ : Is the determinant of the submatrix after eliminating (deleting) the row and column where A32 is located. π ππ [ π¨ππ π¨ππ π¨ππ ] = [π¨ππ π¨ππ − π¨ππ π¨ππ ] = −ππ π¨ππ The Matrix of Minors [π¨]πππππ π = [−π π π π π π] −ππ π The Matrix of Cofactors Change the sign of the elements found in the odd locations in the matrix π¨ππ [π¨] = [π¨ππ π¨ππ π [π¨]πππ = [π π π¨ππ π¨ππ π¨ππ π¨ππ π¨ππ ] π¨ππ −π π π −π] ππ π Adjoint of a Matrix Is found by getting the transpose of a matrix: exchange the row number with the column number π π [π¨]ππ π = [−π π π −π π ππ] π Determinant of Matrix [A] π |π¨| = |π π π π π π −π| = π(π) + π(π) = ππ π Inverse of Matrix [A] : [π¨−π ] = [π¨]ππ π |π¨| π π π π −π π = π ππ π −π [ π ππ π π π] To check if the calculated matrix is the inverse of the given matrix: [π¨][π¨−π ] π [π¨] = [π π π π π π −π] π π = π° = [π π πππ [π¨][π¨−π ] π π π π π] π π π −π [π¨−π ] = π π [π π π = [π π π π π π] π π π π π π ππ −π π] ππ Vector Differentiation For this part of the discussion, it is advantageous for the reader to have recalled a bit of calculus. Some examples of ordinary differentiation can easily be found, π ππ ππππ ππ "π‘βπ πππππ£ππ‘ππ£π ππ … π€ππ‘β πππ ππππ‘ π‘π π₯" ππ₯ Definition of a Derivative: π π(π + βπ) − π(π) βπ π(π) = π₯π’π¦ = π₯π’π¦ βπ →π βπ →π βπ π π βπ Y-axis Y-axis ΔY dY ΔX dX X-axis X-axis π π πΌπ₯ π = πΌππ₯ π−1 πππ { π(π₯) = π₯ , ππ₯ πΌ = ππππ π‘πππ‘ π π₯ π = π π₯ ln π πππ π(π₯) = π π₯ ππ₯ Derivative of alpha x to the n w/r to x π ππ’ π = ππ ππ’ πππ π(π’) = π ππ’ , ππ’ Derivative of e to the au w/r to u Derivative of a to the x w/r to x π sin π = cos π πππ π(π) = sin π ππ Derivative of sine x w/r to theta Assignment: 1. 2. Simple examples of π cos π = ? ππ π sec π = ? ππ π2 π₯ π =? ππ₯ 2 π π π₯ = ππ₯ π−1 ππ₯ 1. π 3 π₯ = 3π₯ 2 , ππ₯ π −2 π₯ = −2π₯ −3 ππ₯ , π 1 (2π₯ 2 + π₯ 3 ) = 4π₯ + π₯ 2 ππ₯ 3 Note that, π 1 π π 1 3 (2π₯ 2 ) + (2π₯ 2 + π₯ 3 ) = ( π₯ ) = 4π₯ + π₯ 2 ππ₯ 3 ππ₯ ππ₯ 3 Example π π ′ π (π₯′ + π₯) = (π₯ ) + (π₯) = 1 + 0 = 1 ππ₯ ππ₯ ππ₯ Example Example π π π ′ (π₯ − π₯′) = (π₯) − (π₯ ) = 1 − 0 = 1 ππ₯ ππ₯ ππ₯ π π π (π₯ − π₯′) = (π₯) − (π₯ ′ ) = 0 − 1 = −1 ππ₯′ ππ₯′ ππ₯ ′ π 1 π (π(π₯))−1 = − π(π₯) ( )= ππ₯ π(π₯) ππ₯ −2 π π(π₯) ππ₯ π 1 π −1 π 1 ( ) = π₯ = −π₯ −2 π₯ = − 2 ππ₯ π₯ ππ₯ ππ₯ π₯ The derivative of x w/r to x is one, π π₯ = 1, ππ₯ π π¦ = 1, ππ¦ π π π₯= π₯ π¦ 0 = π₯(0)π¦ −1 = 0 ππ¦ ππ¦ Rewriting the general rule, π 1 π (π(π₯ ′ ))−1 = − π(π₯ ′ ) ( ) = ππ₯ ′ π(π₯ ′ ) ππ₯ ′ −2 π π(π₯ ′ ) ππ₯ ′ For π(π₯ ′ ) = π₯ − π₯ ′ π 1 π π (π₯ − π₯ ′ )−1 = −(π₯ − π₯ ′ )−2 ′ (π₯ − π₯ ′ ) = (π₯ − π₯ ′ )−2 ( ) = ′ ′ ′ ππ₯ π₯ − π₯ ππ₯ ππ₯ π 1 1 ( ) = ′ ′ (π₯ − π₯ ′ )2 ππ₯ π₯ − π₯ Use this to remind that “the derivative of a one-dimensional potential is the negative of the electric field. Simple examples of 2. π ππ₯ π = ππ ππ₯ ππ₯ π ππ₯ π = ππ ππ₯ , ππ₯ Simple examples of π −2π₯ π = −2π −2π₯ ππ₯ π π [π(π₯)]π = π[π(π₯)]π−1 π(π₯) ππ₯ ππ₯ 3. 1 π 3 1 3 −2 3 √2π₯ 2 − = (2π₯ 2 − ) (4π₯ + 2 ) ππ₯ π₯ 2 π₯ π₯ Simple examples of 4. π π π [π(π₯)π(π₯)] = π(π₯) [π(π₯)] + π(π₯) [π(π₯)] ππ₯ ππ₯ ππ₯ π 2 −πΌπ₯ π(π₯) = π₯ 2 [π₯ π ] π€βπππ { π(π₯) = π −πΌπ₯ ππ₯ π 2 −πΌπ₯ π 2 π −πΌπ₯ [π₯ π ] = π −πΌπ₯ [π₯ ] + π₯ 2 [π ] ππ₯ ππ₯ ππ₯ π 2 −πΌπ₯ [π₯ π ] = π −πΌπ₯ (2π₯) + π₯ 2 [−πΌ(π −πΌπ₯ )] ππ₯ π 2 −πΌπ₯ [π₯ π ] = −πΌπ₯ 2 π −πΌπ₯ + 2π₯π −πΌπ₯ ππ₯ And some examples on partial differentiation, π π₯ π¦ = π₯π¦ π₯−1 ππ¦ π ππ ππ π π = ππππ π π ππ ππ π ππ π π₯ π¦ = π¦ π₯ ln π¦ ππ₯ π 2 −πΌπ₯ 2 2 π = π₯ 4 π −πΌπ₯ 2 ππΌ π2 − π ππ₯ 2 π2 − π ππ₯ 2 π₯2+ π¦2 π₯2+ π¦2 π π − [ π ππ₯ ππ₯ = = [ π₯ 2 + π¦2 π (−2π₯)] π − ππ₯ ]= π₯ 2 + π¦2 π [−2π₯ π − ππ₯ + (−2π₯) [ π₯2+ π¦2 π − π ππ₯ ] π₯2+ π¦2 ] Vector Differential Operator Introduce the operator nabla or del β = π Μ π π ππ Μ + π π ππ + πΜ π ππ Introduce the Laplacian operator βπ π = ππ πππ ππ + πππ ππ + πππ Example β π(π₯) π€βπππ π(π₯) = − ∇ 1 π₯ β π(π₯) = ππππππππ‘ ππ π(π₯) ∇ β π(π₯) = (π₯Μ ∇ π ππ₯ β∇ π(π₯) = π₯Μ + π¦Μ π ππ¦ + π§Μ π 1 ) (− ) ππ§ π₯ π 1 1 (− ) = π₯Μ ( 2 ) ππ₯ π₯ π₯ Gradient The gradient of a scalar function is a vector function Example βπ π(π) π€βπππ π(π) = βπ π(π) = (π₯Μ π ππ₯ 1 1 = πππ π = √π₯ 2 + π¦ 2 + π§ 2 π √π₯ 2 + π¦ 2 + π§ 2 + π¦Μ π ππ¦ + π§Μ π 1 )[ ] ππ§ √π₯ 2 + π¦ 2 + π§ 2 1 1 1 π[ ] π[ ] π[ ] √π₯ 2 + π¦ 2 + π§ 2 √π₯ 2 + π¦ 2 + π§ 2 √π₯ 2 + π¦ 2 + π§ 2 π₯Μ + π¦Μ + π§Μ ππ₯ ππ¦ ππ§ βπ β π(π) = ( ) Note that: For the first term 1 π[ ] 2 1 3 π 1 √π₯ + π¦ 2 + π§ 2 π₯Μ = π₯Μ (π₯ 2 + π¦ 2 + π§ 2 )−2 = − (π₯ 2 + π¦ 2 + π§ 2 )−2 (2π₯)π₯Μ ππ₯ ππ₯ 2 1 π[ ] √π₯ 2 + π¦ 2 + π§ 2 π₯Μ = − ππ₯ π₯π₯Μ 3 = − (π₯ 2 + π¦ 2 + π§ 2 )2 π₯π₯Μ π3 For the second term 1 π[ ] 2 1 3 π 2 1 √π₯ + π¦ 2 + π§ 2 (π₯ + π¦ 2 + π§ 2 )−2 = − (π₯ 2 + π¦ 2 + π§ 2 )−2 (2π¦)π¦Μ π¦Μ = π¦Μ ππ¦ ππ¦ 2 π[ π¦Μ √π₯ 2 1 ] + π¦2 + π§2 = − ππ¦ π¦π¦Μ (π₯ 2 + π¦ 2 + 3 π§ 2 )2 = − π¦π¦Μ π3 For the first term 1 π[ ] 2 1 3 π 1 √π₯ + π¦ 2 + π§ 2 π§Μ = π§Μ (π₯ 2 + π¦ 2 + π§ 2 )−2 = − (π₯ 2 + π¦ 2 + π§ 2 )−2 (2π§)π§Μ ππ§ ππ§ 2 1 π[ ] √π₯ 2 + π¦ 2 + π§ 2 π§Μ = − ππ§ π§π§Μ (π₯ 2 + π¦ 2 + The final expression is obtained by adding all 3 terms 3 π§ 2 )2 = − π§π§Μ π3 β π(π) = − ∇ π₯π₯Μ + π¦π¦Μ + π§π§Μ π 1 = − 2 = − 2 πΜ 3 π ππ π Finally, 1 1 βπ ( ) = − πΜ π π2 Divergence The divergence of a vector function is a scalar function ββ β π β = (π Μ π π ππ₯ Μ + π π ππ¦ β β π β = π + πΜ π )β ππ§ ππΉπ¦ ππΉπ₯ + ππ₯ ππ¦ Example β β π β = π Μ πΉπ₯ π + Μ + πΉπ¦ π ππΉπ§ ππ§ + πΉπ§ πΜ